Cobalt catalyzed carboxylation reaction of saturated hydrocarbons with CO in the presence of K2S2O8 and TFA under mild conditions - Asadullah, Mohammad; Taniguchi, Yuki; Kitamura, Tsugio; Fujiwara, Yuzo (Tetrahedron letters, 1999)
Cobalt(II) acetate (Co(OAc)(2)) has been found to be an efficient catalyst for the carboxylation reaction of saturated hydrocarbons with CO to yield the corresponding carboxylic acids in high yields in the presence of K2S2O8 and CF3COOH. About 89.5% conversion of propane is obtained in this reaction. The activation parameters of the reaction of propane have been determined by Arrhenius and Eyring plots. (C) 1999 Elsevier Science Ltd. All rights reserved.